Sobre a noção de atração em Maurice Blanchot - Maia Neto, Paulo Carneiro (2022)
Maurice Blanchot's dialogues with Kafka, Rilke and Nietzsche run through a certain number of artistic expressions asking how the alliance between philosophy and art can enrich the communication of the labor. For that, the reflections around the inspired creative will reveal its enigmatic demands by which the supposed centralized interiority of the experience perishes. From literature to plastic arts, from sculpture to cinema, from fragments to rhythm, everything revolves around the disappearance imposed by the secretive impulses of creation